Behavioral effects of aminochrome and dopachrome injected in the rat substantia nigra. - Díaz-Véliz, G; Mora, S; Dossi, M; Gómez, P; Arriagada, C; Montiel, J; Aboitiz, F; Segura-Aguilar, J (2002)
The exact mechanism of cell death in neurodegenerative diseases remains obscure, although there is evidence that their pathogenesis may involve the formation of free radicals originating from the oxidative metabolism of catecholamines. The purpose of this study was to evaluate the degree of neurodegenerative changes and behavioral impairments induced by unilateral injection into the rat substantia nigra of cyclized o-quinones, aminochrome and dopachrome, derived from oxidizing dopamine and L-DOPA, respectively, with Mn(3+)-pyrophosphate complex. The behavioral changes were compared with those induced after selective lesions of dopaminergic neurons with 6-hydroxydopamine (6-OHDA). Intranigral injection of aminochrome and dopachrome produced impairment in motor and cognitive behaviors. The behavioral impairment was also revealed by apomorphine-induced rotational asymmetry. Apomorphine (0.5 mg/kg sc) significantly increased rotational behavior in rats injected with aminochrome and dopachrome. These rats presented a clear motor bias showing a significant contralateral rotation activity, similar but less vigorous that in rats injected with 6-OHDA. The avoidance conditioning was seriously impaired in rats injected with aminochrome and dopachrome although only dopachrome-injected rats showed a similar hypomotility to 6-OHDA-injected rats. The behavioral effects were correlated to the extent of striatal tyrosine hydroxylase (TH)-positive fiber loss. Rats receiving unilateral intranigral aminochrome and dopachrome injections exhibited a 47.9+/-5.1% and a 39.7+/-4.4% reduction in nigrostriatal TH-positive fiber density. In conclusion, this study provided evidence that oxidizing DA and L-DOPA to cytotoxic quinones, aminochrome and dopachrome appears to be an important mediator of oxidative damage in vivo.